The silent life of things : reading and representing commodified objecthood - Rogobete, Daniela; Sell, Jonathan P. A.; Munton, Alan, 1945- (Cambridge Scholars Publishing, 2015)
The ever-growing interest in the analysis of materiality has found its expression in many studies of objects and objecthood, of things and "thingness". Combining cultural, phenomenological, semiotic, and philosophical approaches, this collection of eleven essays proposes a journey into "the silent life of things", into those aspects of materiality that are not immediately visible and require both increased attention and a sense of intuition. It focuses on the subtle changes that materiality operates upon our subjectivity and upon our status as producers, users, possessors, negotiators and mani